Validity Of the Human Circulatory System Booklets as an Independent Teaching Material for Natural Science in Class VIII Junior High School - Yulia Ramadhani; Helendra Helendra; Siska Alicia Farma; Syamsurizal Syamsurizal (Bioeducation Journal, 2021)
Education important element develop knowledge make shape one’s character. Quality of education can be improved by paying attention to the curriculum and learning media used. 2013 curriculum based science textbooks and student worksheets are a medium used by student to study natural science in class VIII SMPN 11 Padang. The availability of learning resources at school is still lacking, so that students are less motivated in learning science, in addition to the lack of availability of learning resources, other factors that cause low motivation of students because textbooks are used thickly and are difficult to carry anywhere. Based on the weaknesses that were found, the booklet was developed as an independent learning resources of natural science in class VIII junior high school. Booklet media development is made as attractive as possible, so that students are motivated to learn science. This development research uses a Plomp development model consisting of (preliminary research), (development and prototyping phase), and assessment phase (assessment phase). Data analysis is qualitative and quantitative. Booklet development stage is validated by 2 validators. At the assessment stage uses one to one evaluation by 3 student in class VIII of the SMPN 11 Padang which has high, medium, and low academic abilities. Validity test result obtained of 87,62% with very valid criteria and results of one to one evaluation showed that the developed booklet had an attractive appearance and language that was easy to understand, sothat students were interested in using booklets in the learning process. Based on this, it can be concluded that the human circulatory system booklet as an independent teaching material of natural science developed is valid and suitable for use in the learning process.